”Being Bilingual Means Being a Foreigner”. Categorizing Linguistic Diversity among Students in Danish Higher Education - Holmen, Anne (HERMES - Journal of Language and Communication in Business, 2014)
One of the effects of the internationalization of Danish higher education is a more mobile and linguistically heterogeneous student population aiming at both the national and international labor market. At the same time efforts to increase participation in higher education among domestic students have resulted in a more diverse student body in terms of social and ethnic background. To some extent the two groups of students overlap, but they are treated very differently by the university administration. Whereas students with international experience are counted and categorized as such, and are offered language courses before going abroad or when arriving in Denmark, minority students are either part of the mainstream or identifi ed as in need of remedial courses. The latter does not correspond very well with the general shift towards more learner-centered approaches in higher education, which potentially opens up to a resource perspective on multilingual students’ language background. The present paper is a literature review focusing on the various labels used when categorizing students according to their linguistic background. The purpose of this is to raise awareness about labelling as a sensitive issue and to propose a multilingual pedagogical framework for students to benefit from their full language potential during their academic studies.